Preparation method and application of Ir-based supported electrolyzed water catalyst capable of realizing mass production
By introducing pressure-assisted regulation methods during the catalyst preparation process, the problem of uneven nanoparticles of Ir-based supported electrolytic catalysts and weak support interactions is solved, high activity and stability of the catalyst are achieved, and the advantages of large-scale production are provided.
Patent Information
- Application Number
- CN202510074996.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing preparation methods for Ir-based supported electrolytic catalysts have problems such as uneven nanoparticles size, poor consistency, and weak interaction between carrier and nanoparticles, resulting in insufficient activity and stability of the catalyst, making it difficult to achieve large-scale production.
Using a pressure-assisted regulation method, the organic Ir salt precursor is mixed with the carrier, and treated in an inert atmosphere by high-temperature annealing, the agglomeration and growth of nanoparticles are restricted, so that they are uniformly loaded on the surface of the carrier, and the interaction between the nanoparticles and the carrier is enhanced.
The uniform loading and small size control of Ir nanoparticles is achieved, which improves the activity and stability of the catalyst, avoids the formation of by-products and additional purification steps, and has the characteristics of large-scale production.
Smart Images

Figure CN119800410A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and relates to a preparation method and application of an Ir-based supported water electrolysis catalyst that can be mass-produced. Background Art
[0002] With the rapid development of the global economy, the consumption of fossil fuels such as coal, oil and natural gas, which are the main energy sources, has also increased dramatically. People are constantly turning their attention to new clean energy such as solar energy, wind energy and hydrogen energy. Among them, clean energy represented by hydrogen energy has the advantages of high combustion calorific value, high energy density and low pollution, and has attracted more and more attention. At present, one of the main ways to obtain hydrogen energy is to produce hydrogen by electrolysis of water. By using H2 as an energy carrier, the electricity generated by renewable energy is stored in the chemical bonds of H2 through the electrochemical cracking of water.
[0003] Proton exchange membrane water electrolysis (PEMWE) technology is one of the key technologies for producing green hydrogen from renewable energy. Its anode-side oxygen evolution reaction (OER) requires a catalyst with excellent performance to accelerate the water electrolysis process. Ir-based materials are the first choice for anode catalysts of proton exchange membrane water electrolysis (PEMWE) due to their high stability and activity under acidic conditions. However, the scarcity and high cost of Ir have hindered the widespread application of PEMWE. Therefore, reducing the amount of Ir by designing supported catalysts while improving its utilization efficiency and performance is of great significance to promoting the large-scale application of PEMWE.
[0004] At present, most supported catalysts are prepared by solvent thermal methods such as polyol reduction method. For example, patent CN116516406 A prepared a Ti4O7-loaded IrO x However, this method requires the selection of specific solvents and additives for different materials, and some organic solvents may be toxic or environmentally harmful; at the same time, this method has difficulty in maintaining uniform nanoparticle size and agglomeration during heat treatment, resulting in reduced utilization efficiency of active sites. In addition, problems such as nanoparticle shedding and growth may occur during the reaction of supported catalysts prepared by the polyol method, indicating that the interaction between the support and the nanoparticles is weak and still needs to be further strengthened. Therefore, how to design a simple and efficient method to prepare supported catalysts with controllable nanoparticle size and strong nano-support interaction is still a problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a mass-producible Ir-based supported electrolytic water anode catalyst and its application in view of the shortcomings of the existing Ir-based supported electrolytic water catalyst preparation method. The method introduces pressure-assisted regulation, and after mixing the organic Ir salt precursor and the carrier, the agglomeration and growth of nanoparticles during the high-temperature annealing process are limited by the pressure environment, and small-sized nanoparticles are uniformly loaded on the surface of the carrier, thereby strengthening the interaction between the nanoparticles and the carrier, adjusting the electronic structure of Ir, and having excellent performance as an anode catalyst in an electrolytic cell. The present invention avoids the formation of by-products caused by the use of organic solvents, and does not require additional purification steps. In addition, the present invention increases the feed ratio by 20 times year-on-year, and can also achieve the synthesis of catalysts on a gram scale, which can be extended to actual production to achieve large-scale production.
[0006] The technical solution of the present invention is: A method for preparing a mass-producible Ir-based supported water electrolysis catalyst, the method comprising the following steps: (1) adding an organic Ir salt precursor and a carrier to a mixed solvent, mixing, ultrasonically stirring for 20 to 40 minutes, and drying and grinding to obtain a mixed powder; The mixed solvent is composed of anhydrous ethanol / deionized water; 0.01 mmol to 0.1 mmol of organic Ir salt precursor is added to every 10 ml of the mixed solvent; the mass ratio of the organic Ir salt precursor to the carrier is 1:1.6 to 25:1; (2) moving the mixed powder obtained in the previous step into a high pressure furnace, heating it to 500° C. to 1000° C., annealing it in an inert atmosphere for 0.5 h to 48 h, and cooling it to room temperature to obtain the Ir-based supported water electrolysis catalyst with different loadings; Among them, the pressure of the inert atmosphere is 0.1 MPa~50 MPa higher than the standard atmospheric pressure; as the pressure of the inert gas increases, the particle size of the Ir nanoparticles tends to decrease.
[0007] The organic Ir salt precursor is acetylacetonate.
[0008] The carrier material is one of nano-Ti powder, indium tin oxide (ITO), and antimony-doped tin oxide graphite (ATO); preferably nano-Ti powder; the size of the carrier material is 10-200 nm.
[0009] The volume ratio of the mixed solvent anhydrous ethanol / deionized water is 1:2-2:1, preferably 1:1.
[0010] The method for drying the mixed solution in step (1) is a rotary evaporation solvent drying method or a blast oven drying method. After drying, the solid powder is ground for 5 to 10 minutes.
[0011] The heat treatment annealing temperature in step (2) is preferably 600°C~800°C, the heat treatment inert atmosphere pressure is preferably 0.1 MPa~10 MPa higher than the standard atmospheric pressure and the standard atmospheric pressure in a closed space, and the inert gas is argon or nitrogen; the heating rate is 1°C / min~50°C / min, and the annealing time is preferably 1 h~24 h.
[0012] The catalyst comprises a carrier and small-sized Ir nanoparticles loaded on the carrier; the loading amount of the Ir-based nanoparticles is 20wt% to 90wt%; the average particle size of the small-sized nanoparticles is 1 to 10 nm; and as the pressure of the inert gas increases, the particle size of the Ir nanoparticles tends to decrease.
[0013] The output of the catalyst reaches the gram level.
[0014] The Ir-based supported water electrolysis catalyst prepared by the method is used as an anode catalyst in an electrolytic cell.
[0015] The present invention can be used in, but is not limited to, proton exchange membrane electrolyzers. Due to its advantage of being scalable, it can be used to solve the problems of complex process, catalyst cost, and activity and durability in the actual production process of supported catalysts.
[0016] The essential features of the present invention are: The mass-producible Ir-based supported water electrolysis catalyst provided by the present invention has a smaller Ir nanoparticle size and is evenly distributed on a carrier. The catalyst preparation method mainly comprises the following steps: fully mixing an organic Ir salt precursor with a carrier, and performing thermal decomposition reduction to preliminarily obtain an Ir cluster supported on the carrier; then the cluster is subjected to high-temperature calcination treatment and heat preservation for a period of time under an inert atmosphere under pressure, so as to achieve the preparation of a small-sized and evenly distributed Ir-based supported catalyst. The preparation method has a simple process and good universality, and can easily achieve large-scale mass production of Ir-based supported catalyst synthesis. Moreover, due to the presence of pressure, the sintering and growth of Ir nanoparticles during the heat treatment process can be effectively inhibited, and the interaction between the nanoparticles and the carrier can be strengthened, so as to achieve the loading of nanoparticles less than 10 nm on the carrier, which has important scientific and engineering significance in improving the stability of the catalyst.
[0017] The beneficial effects of the present invention are: (1) Based on the traditional high-temperature annealing, the invention innovatively introduces pressure-assisted regulation. Through high-temperature annealing, the Ir salt precursor is fully thermally decomposed and reduced to form Ir clusters, and the size of the nanoparticles is limited under the action of pressure, which inhibits the migration and growth of the nanoparticles, so that small-sized nanoparticles are more evenly loaded on the carrier. In the synthesis method of the prior art, some auxiliary drugs or template materials are usually added, and the by-products need to be removed through subsequent purification steps to achieve a similar effect. Secondly, the small-sized nanoparticles synthesized by applying appropriate pressure and temperature have a strong interaction with the carrier, which can effectively adjust the Ir electronic structure and improve the utilization rate of active sites, thereby improving the activity and stability of the catalyst.
[0018] (2) The organic matter in the acetylacetonate precursor can be reduced at high temperature to form a carbon matrix, and loaded with small-sized Ir nanoparticles together with related carriers, so that the catalyst has a smaller mass transfer resistance in practical applications and greatly improves the utilization rate of precious nanoparticles, making the catalyst more effective in application. When the current density is 10 mA cm -2 When the overpotential of Ir@ nano-Ti powder is only 271 mV (M load =0.05 mg Ir cm -2 ), low Ir loading can also effectively alleviate the current Ir resource scarcity problem.
[0019] (3) The present invention avoids the formation of by-products caused by the use of organic solvents, does not require additional purification steps, and can be easily synthesized at the gram scale. In summary, the method of the present invention has the advantages of simple preparation process, universality, no complicated pretreatment process and the addition of other chemical substances, etc., which makes its large-scale production feature have broader application prospects and engineering significance in commercial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a low-magnification transmission electron microscope image of the mass-producible Ir@nano-Ti powder catalyst prepared in Example 1.
[0021] Figure 2 This is a high-magnification transmission electron microscope image of the mass-producible Ir@nano-Ti powder catalyst prepared in Example 1.
[0022] Figure 3 This is the LSV curve of the mass-producible Ir@nano-Ti powder catalyst prepared in Example 1. DETAILED DESCRIPTION
[0023] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the spirit and essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all belong to the scope of the present invention.
[0024] Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.
[0025] Embodiment 1: (1) 0.053 mmol (26.26 mg) of iridium acetylacetonate and 40 mg of nano-Ti powder were mixed, and 15 mL of anhydrous ethanol and 15 mL of deionized water were added to dissolve the Ir salt precursor. Ultrasonic treatment was performed for 30 min. After sufficient mixing and dissolution, the mixture was dried using a rotary evaporator. The solid sample was scraped off the eggplant-shaped bottle and fully ground for 10 minutes to fully mix the nano-salt precursor and the nano-Ti powder. The obtained powder was placed in a porcelain boat and wrapped with copper foil for later use. (2) The copper foil and the wrapped powder were then placed in a high-pressure furnace, heated to 600°C at a rate of 10°C / min in a nitrogen atmosphere at 1 MPa above the standard atmospheric pressure, and kept at that temperature for 1 h, and then naturally cooled to room temperature to obtain a black product; Figure 1 The figure shows a low-magnification transmission electron micrograph of the mass-producible Ir@nano-Ti powder catalyst, which shows that the overall morphology of the catalyst is composed of nano-Ti powder loaded with Ir nanoparticles. The nanoparticles are uniform in size and evenly loaded on the nano-Ti powder carrier without obvious agglomeration, which can effectively expose their active sites. Figure 2 Shown is a high-magnification transmission electron micrograph of a mass-producible Ir@nano-Ti powder catalyst, demonstrating that the catalyst as a whole is composed of Ir nanoparticles loaded on nano-Ti powder. Combined with the figure, it can be seen that the average particle size of the Ir nanoparticles is less than 5 nm. The small and uniform particle size allows the catalyst to expose a larger electrochemical active area, greatly improving the exposure rate of the active sites.
[0026] Afterwards, the obtained mass-producible Ir@ nano-Ti powder catalyst was tested for oxygen evolution reaction (OER) performance in 150 mL O2-saturated 0.5 mol / L H2SO4 solution using Shanghai Chenhua CHI760E electrochemical workstation (reversible hydrogen electrode as reference electrode, platinum sheet as counter electrode), as shown in Figure 2. Figure 3 As shown, when the current density is 10 mA cm -2 When the overpotential of Ir@ nano-Ti powder is only 271 mV (M load =0.05 mg Ir cm -2 ).
[0027] Embodiment 2: (1) 1.072 mol (0.525 g) of iridium acetylacetonate and 0.8 g of nano-Ti powder were mixed, and 300 mL of anhydrous ethanol and 300 mL of deionized water were added to dissolve the Ir salt precursor. Ultrasonic treatment was performed for 30 min. After sufficient mixing and dissolution, the mixture was dried using a rotary evaporator. The solid sample was scraped off the eggplant-shaped bottle and fully ground for 10 minutes to fully mix the nano-salt precursor and the nano-Ti powder. The obtained powder was placed in a porcelain boat and wrapped with copper foil for later use. Then, the copper foil and the wrapped powder were placed in a high-pressure furnace, heated to 600°C at a rate of 10°C / min in a nitrogen atmosphere 1 MPa higher than the standard atmospheric pressure, and kept at that temperature for 1 hour, and then naturally cooled to room temperature to obtain a black product with a gram-high yield. Embodiment 3: (1) Mix 0.053 mmol (26.26 mg) iridium acetylacetonate and 40 mg ITO, add 15 mL anhydrous ethanol and 15 mL deionized water to dissolve the Ir salt precursor, ultrasonicate for 30 min, fully mix and dissolve, dry using a rotary evaporator, scrape the solid sample from the eggplant-shaped bottle and grind it for 10 minutes. Fully mix the nano salt precursor and nano Ti powder, put the obtained powder into a porcelain boat and wrap it with copper foil for later use; (2) The copper foil and the wrapped powder were then placed in a high-pressure furnace, heated to 650°C at a rate of 10°C / min in a nitrogen atmosphere 2 MPa higher than the standard atmospheric pressure, and kept at that temperature for 5 h, and then naturally cooled to room temperature to obtain a black product; Embodiment 4: (1) Mix 0.053 mmol (26.26 mg) iridium acetylacetonate and 40 mg ATO, add 15 mL anhydrous ethanol and 15 mL deionized water to dissolve the Ir salt precursor, ultrasonicate for 30 min, fully mix and dissolve, dry using a rotary evaporator, scrape the solid sample from the eggplant-shaped bottle and grind it for 10 minutes. Fully mix the nano salt precursor and nano Ti powder, put the obtained powder into a porcelain boat and wrap it with copper foil for later use; (2) The copper foil and the wrapped powder were then placed in a high-pressure furnace, heated to 650°C at a rate of 10°C / min in a nitrogen atmosphere 5 MPa higher than the standard atmospheric pressure, and kept for 2 h, and then naturally cooled to room temperature to obtain a black product; Embodiment 5: (1) Mix 0.053 mmol (26.26 mg) iridium acetylacetonate and 50 mg nano-Ti powder, add 15 mL anhydrous ethanol and 15 mL deionized water to dissolve the Ir salt precursor, ultrasonicate for 30 min, fully mix and dissolve, dry using a rotary evaporator, scrape the solid sample from the eggplant-shaped bottle and grind it for 10 minutes. Mix the nano-salt precursor and nano-Ti powder thoroughly, put the obtained powder into a porcelain boat and wrap it with copper foil for later use; (2) The copper foil and the wrapped powder were then placed in a high-pressure furnace, heated to 800°C at a rate of 10°C / min in a nitrogen atmosphere at 5 MPa above the standard atmospheric pressure, and kept at that temperature for 1 h, and then naturally cooled to room temperature to obtain a black product; Embodiment 6: (1) Mix 0.053 mmol (26.26 mg) iridium acetylacetonate and 40 mg ATO, add 15 mL anhydrous ethanol and 15 mL deionized water to dissolve the Ir salt precursor, ultrasonicate for 30 min, fully mix and dissolve, dry using a rotary evaporator, scrape the solid sample from the eggplant-shaped bottle and grind it for 10 minutes. Fully mix the nano salt precursor and nano Ti powder, put the obtained powder into a porcelain boat and wrap it with copper foil for later use; (2) The copper foil and the wrapped powder were then placed in a high-pressure furnace, heated to 700°C at a rate of 10°C / min in a nitrogen atmosphere at a pressure 10 MPa higher than the standard atmospheric pressure, and kept at that temperature for 5 h, and then naturally cooled to room temperature to obtain a black product; Embodiment 7: (1) Mix 0.053 mmol (26.26 mg) iridium acetylacetonate and 40 mg ATO, add 15 mL anhydrous ethanol and 15 mL deionized water to dissolve the Ir salt precursor, ultrasonicate for 30 min, fully mix and dissolve, dry using a rotary evaporator, scrape the solid sample from the eggplant-shaped bottle and grind it for 10 minutes. Fully mix the nano salt precursor and nano Ti powder, put the obtained powder into a porcelain boat and wrap it with copper foil for later use; (2) The copper foil and the wrapped powder were then placed in a high-pressure furnace, heated to 900°C at a rate of 10°C / min in a nitrogen atmosphere 2 MPa higher than the standard atmospheric pressure, and kept at that temperature for 1 h, and then naturally cooled to room temperature to obtain a black product; Matters not covered by the present invention are known technologies.
Claims
1. A method for preparing a mass-producible Ir-based supported water electrolysis catalyst, characterized in that: The method comprises the following steps: (1) adding an organic Ir salt precursor and a carrier to a mixed solvent, mixing, ultrasonically stirring for 20 to 40 minutes, drying, and grinding to obtain a mixed powder; The mixed solvent is composed of anhydrous ethanol / deionized water; 0.01 mmol to 0.1 mmol of organic Ir salt precursor is added to every 10 ml of the mixed solvent; the mass ratio of the organic Ir salt precursor to the carrier is 1:1.6 to 25:1; The organic Ir salt precursor is acetylacetonate; The carrier material is one of nano-Ti powder, indium tin oxide (ITO), and antimony-doped tin oxide graphite (ATO); preferably nano-Ti powder; the size of the carrier material is 10-200 nm; (2) moving the mixed powder obtained in the previous step into a high pressure furnace, heating it to 500° C. to 1000° C., annealing it in an inert atmosphere for 0.5 h to 48 h, and cooling it to room temperature to obtain the Ir-based supported water electrolysis catalyst with different loadings; The pressure of the inert atmosphere is 0.1 MPa~10 MPa higher than the standard atmospheric pressure.
2. The method for preparing a mass-producible Ir-based supported water electrolysis catalyst as claimed in claim 1, characterized in that: The volume ratio of the mixed solvent anhydrous ethanol / deionized water is 1:2~2:
1.
3. The method for preparing a mass-producible Ir-based supported water electrolysis catalyst as claimed in claim 1, characterized in that: The inert gas is argon or nitrogen.
4. The method for preparing a mass-producible Ir-based supported water electrolysis catalyst as claimed in claim 1, characterized in that: The method for drying the mixed solution in step (1) is a rotary evaporation solvent drying method or a blast oven drying method. After drying, the solid powder is ground for 5 to 10 minutes.
5. The method for preparing a mass-producible Ir-based supported water electrolysis catalyst as claimed in claim 1, characterized in that: The heat treatment annealing temperature in step (2) is preferably 600°C to 800°C, the heat treatment inert atmosphere pressure is 0.1 MPa to 10 MPa higher than the standard atmospheric pressure; the heating rate is 1°C / min to 50°C / min, and the annealing time is 1 h to 24 h.
6. The method for preparing the mass-producible Ir-based supported water electrolysis catalyst as claimed in claim 1, characterized in that: The catalyst comprises a carrier and small-sized Ir nanoparticles loaded on the carrier; the loading amount of the Ir-based nanoparticles is 20wt% to 90wt%; the average particle size of the small-sized nanoparticles is 1 to 10 nm; and the particle size of the carrier is 10-200 nm.
7. The method for preparing the mass-producible Ir-based supported water electrolysis catalyst as claimed in claim 1, characterized in that: As the pressure of the inert gas increases, the particle size of Ir nanoparticles decreases.
8. The method for preparing the mass-producible Ir-based supported water electrolysis catalyst as claimed in claim 1, characterized in that: The production volume of the catalyst reaches the gram level.
9. The use of an Ir-based supported water electrolysis catalyst prepared by the method of claim 1, characterized in that: Used as anode catalyst in electrolyzers.
Citation Information
Patent Citations
Preparation and application of supported Ir group cluster catalyst with high electro-catalytic property
CN115976561A
Iridium and / or ruthenium-based catalyst for water electrolysis and preparation method thereof
CN116463665A
Preparation method of platinum-based alloy catalyst with small size and high loading capacity
CN117577864A
Preparation method and device for metal oxide supported iridium / ruthenium-based catalyst
WO2022188278A1